Two-Pore Channels: Catalyzers of Endolysosomal Transport and Function - Grimm, Christian; Chen, Cheng-Chang; Wahl-Schott, Christian; Biel, Martin (Frontiers in Pharmacology, 2017)
Two-pore channels (TPCs) have recently emerged as a novel class of non-selective cation channels in the endolysosomal system. There are two members in the human genome, TPC1 and TPC2. Studies with TPC knockout and knockdown models have revealed that these channels participate in the regulation of multiple endolysosomal trafficking pathways which when dysregulated can lead to or influence the development of a range of different diseases such as lysosomal storage, metabolic, or infectious diseases. Two-pore channels have been demonstrated to be activated by different endogenous stimuli, PI(3,5)P2 and NAADP, and ATP has been found to block TPC activation via mTOR. Loss of TPCs can lead to obesity and hypercholesterolemia, and to a slow-down of intracellular virus and bacterial toxin trafficking, it can affect VEGF-induced neoangiogenesis, autophagy, human hair pigmentation or the acrosome reaction in sperm. Moreover, physiological roles of TPCs in cardiac myocytes and pancreatic β cells have been postulated.